STUDY OF THE IMPACT OF FAMILY ENVIRONMENT ON THE EDUCATIONAL ACHIEVEMENT OF STUDENTS STUDYING AT SECONDARY LEVEL - Savita; Singh, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Family, which is the first social institution in a child’s life, plays an important role in his education and personality development. Family environment refers to the mental, social and emotional environment that family members share with each other. It includes the behavior of parents, their level of education, economic status, influence of family values ​​and traditions. All these factors directly or indirectly affect the educational achievement of a student. Parental education and awareness play a major role in the family environment. Educated parents not only understand the educational needs of their children but also provide them with proper guidance. They encourage children to study, create a conducive environment for them to study and help them resolve difficulties. In contrast, uneducated or less educated parents are not able to provide that level of support in their children’s educational life. Economic status is also a major factor in family environment. In families with high economic status, children get books, technical resources and opportunities such as tuition, which help to improve their educational achievement. On the other hand, in economically weak families, children sometimes have to contribute to household chores or employment along with studies, which affects their studies. Apart from this, family structure also affects educational achievement. Children in joint families get social support, but sometimes it may be difficult to concentrate on their studies due to family responsibilities and limited resources. On the other hand, in nuclear families, children’s education may be positively affected due to getting more personal attention from parents. However, tension or separation between parents can have a negative impact on children’s educational achievement. Family values ​​and discipline also have an important influence. Children perform better in a family where education is given priority and time management and discipline are encouraged. On the other hand, a stressful or neglectful family environment can distract children from studying. Thus, it is clear that family environment is the fundamental pillar of students’ academic achievement. A healthy and positive family environment not only improves children’s academic performance but also helps in their overall personality development. Therefore, parents should create an environment for their children that motivates them to learn, think and achieve their goals.